Watching over 21,000 billion euros: Does the ECB Single Supervisory Mechanism affect bank competition in the euro area? - Burkhard Raunig; Michael Sigmund (Oesterreichische Nationalbank (OeNB), 2023)
Under the Single Supervisory Mechanism (SSM), introduced in 2014, systemically important euro area banks with combined assets of about 21,000 billion euros are directly supervised by the ECB. We examine from a static and a dynamic perspective how this fundamental shift to unified supervision under the SSM affects the competitive position of SSM banks. We find that the SSM reduced competition for SSM banks in countries affected by the sovereign debt crisis. Otherwise, the impact of the SSM was limited or competition increased. Furthermore, our results suggest that anti-competitive side effects of the SSM are unlikely to be permanent.
Keywords: D43; E58; G28; 330; ECB Single Supervisory Mechanism; Banking supervision; Competition; Lerner index; Persistence of profits